2018
DOI: 10.1617/s11527-018-1206-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of corrosion level of naturally corroded bars using different cleaning methods, computed tomography, and 3D optical scanning

Abstract: Reliable methods are necessary to assess the corrosion level to establish links between structural performance and reinforcement corrosion in concrete structures. Hence, in this study, a set of naturally corroded bars were subjected to metallic brushing, acid immersion, and sandblasting for rust removal. Additionally, 3D optical, CT scanning, and weight loss measurements were used to evaluate the levels of corrosion. The results indicate that sandblasting is an optimal cleaning method. Weight loss measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 32 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Analyses concerning corrosion phenomenon cover a wide range of research processes in the field of materials science, which are carried out to determine the type of corrosion damage and the causes of corrosion. In the literature [ 2 , 4 , 17 , 35 ], corrosion tests are classified according to various criteria, among them according to the type of conditions in which the tests are performed (i.e., tests in conditions of natural environment and in laboratory conditions). Tests in natural conditions are carried out in corrosive environments such as air, soil, or liquids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses concerning corrosion phenomenon cover a wide range of research processes in the field of materials science, which are carried out to determine the type of corrosion damage and the causes of corrosion. In the literature [ 2 , 4 , 17 , 35 ], corrosion tests are classified according to various criteria, among them according to the type of conditions in which the tests are performed (i.e., tests in conditions of natural environment and in laboratory conditions). Tests in natural conditions are carried out in corrosive environments such as air, soil, or liquids.…”
Section: Methodsmentioning
confidence: 99%
“…Very good physical and chemical properties of steel are the reason for its use in many branches of industry. One of the most significant problems in construction and exploitation of machines is the corrosive destruction of iron alloys [ 1 , 2 , 3 , 4 , 5 ]. The effects of this process are losses—direct ones, related to the costs of damaged materials and construction protection, as well as indirect ones, related to the operation of machines.…”
Section: Introductionmentioning
confidence: 99%
“…The cleaning of the bars was performed following the corresponding recommendations specified in the ASTM (2011). Mechanical cleaning through sandblasting was chosen in this study as the preferred cleaning method according to the findings reported in (Fernandez et al 2018). The cleaning of the bars was performed in an individual sandblasting cabinet designed for the purpose.…”
Section: Corrosion Level Determination 221 Cleaning Methods and Weigmentioning
confidence: 99%
“…As mentioned earlier, the bars loaded in tension were removed after the structural tests. They were cleaned by sandblasting, which was selected as a cleaning method according to the findings in [28]. The sandblasting was performed in an individual cabinet designed for the purpose, by using 5-7 bars of pressure and silica sand.…”
Section: Cleaning Of the Barsmentioning
confidence: 99%